Soil and Root Attributes in Pastures Managed under Different Stocking Rates and Nitrogen Fertilization Levels. Issue 1 (14th February 2019) - da Silva, Hiran Marcelo Siqueira; Dubeux, José Carlos Batista; Silveira, Maria Lúcia; dos Santos, Mércia Virginia Ferreira; de Freitas, Erinaldo Viana; de Almeida, Brivaldo Gomes
Abstract : Core Ideas: Grassland is a widespread agroecosystem in the globe; however, not enough attention has been given to link grazing management to soil health. Grazing management practices greatly impact soil quality. Moderate stocking rate are more adequate to keep grassland stability. Pasture management affects soil physical–chemical properties and root depth distribution. Adjusting grazing pressure and N fertilization are key management tools affecting these responses. This study evaluated the effect of N fertilization and stocking rate (SR) on soil physical and chemical attributes and root depth distribution in grazed elephantgrass ( Pennisetum purpureum Schum. cv. 381) pastures (2009 and 2010). Treatments consisted of three SR (2.0, 3.9, and 5.8 AU ha −1 ; 1 AU = animal unit = 450 kg body weight) and three N doses (0, 150, and 300 kg N ha −1 yr −1 ) on elephantgrass pastures. Response variables included soil bulk density (BD), particle density (PD), total porosity (TP), aggregate stability (AS), water infiltration rate (WIR), light fraction of soil organic matter (LF‐SOM), soil fertility, root length density (RLD), and root biomass. Increased SR resulted in greater BD. Soil bulk density ranged from 1.42 to 1.58 g cm −3 for SR ranging from 2.0 to 5.8 AU ha −1, respectively. The C concentration of the LF‐SOM decreased with increasing SR, ranging from 383 to 174 mg C kg −1 soil. Soil fertility, RLD, and the stock of C and N in the root system varied among soil layers. At the end of 2 yr, SR and N fertilization did not affect TP, WIR, and AS nor influenced soil fertility and root system distribution. Overgrazing led to soil compaction and reduced LF‐SOM, indicating a trend of pasture degradation. Moderate SR resulted in greater LF‐SOM, indicating a positive trend for C accumulation in the long term.